2022
DOI: 10.1177/10781552221139775
|View full text |Cite
|
Sign up to set email alerts
|

A review of the novel tissue factor antibody–drug conjugate: Tisotumab vedotin

Abstract: Objective To review and compare the pharmacology, efficacy, and safety of the novel tissue factor antibody–drug conjugate, tisotumab vedotin Data sources Literature search was performed through PubMed MEDLINE, Google Scholar, ClinicalTrials.gov, and the Food and Drug Administration. Data summary Tisotumab vedotin, a novel tissue factor antibody–drug conjugate, was granted accelerated approval by the US FDA on 20 September 2021 for adult patients with recurrent or metastatic cervical cancer with disease progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…These results encouraged the continuation of the clinical research of TV in the treatment of TF-expressing solid tumours. 26 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These results encouraged the continuation of the clinical research of TV in the treatment of TF-expressing solid tumours. 26 …”
Section: Resultsmentioning
confidence: 99%
“…14,28 Moreover, the frequency of ocular events, including conjunctivitis, was further reduced after the implementation of mitigation measures. 26 The interim analysis of the phase I/II InnovaTV 205 study showed promising activity when TV was used in combination with platinum and pembrolizumab with manageable and non overlapping toxicity profiles 31,32 ORR was 54.5%, 40.6% and 38.3% in patients treated with first line TV + carboplatin, first line TV + pembrolizumab and second/ third line TV + pembrolizumab, respectively. 31 In the last year, the results of KEYNOTE-826 changed the paradigm of first line treatment of advanced/recurrent cervical cancer and pembrolizumab has been approved for patients with CPS ≥ 1 in combination with carboplatinpaclitaxel ± bevacizumab for advanced or recurrent, chemo-naïve, cervical cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations